The case of the “serfdom” condition of phagocytic immune cells - E Ottaviani (Invertebrate Survival Journal, 2012)
In a modern immunological perspective, it may be asserted that the phagocytic cell should not be considered as the "serfdom", but rather the pivot of the immune system. Indeed, the invertebrate immunocyte as well as the vertebrate macrophage play a central role in immunity, inflammation and stress response. The evolutionary conserved immune-neuroendocrine effector system have remained of fundamental importance in defense against pathogens, and its efficiency increased through synergy with the new, clonotipical recognition repertoire in vertebrates.